FORMATION OF FOREIGN LANGUAGE COMMUNICATIVE COMPETENCE IN THE PROCESS OF TEACHING FOREIGN LANGUAGES - SARIEVA ASSEMGUL KYDYRBAEVNA (Foundations and Trends in Modern Learning, 2025)
This article discusses the problems of modern linguodidactics and methods of teaching foreign languages, focusing on the development of communicative competence that ensures active participation in intercultural communication. Many domestic and foreign scholars have studied the theoretical and practical aspects of this topic, defining the essence of foreign language communicative competence, its structure, and the conditions for its formation